(x平方-3)平方-x(x平方-3)-2x平方
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/05 01:04:58
(x平方-3)平方-x(x平方-3)-2x平方(x平方-3)平方-x(x平方-3)-2x平方(x平方-3)平方-x(x平方-3)-2x平方答:(x平方-3)平方-x(x平方-3)-2x平方=(x
(x平方-3)平方-x(x平方-3)-2x平方
(x平方-3)平方-x(x平方-3)-2x平方
(x平方-3)平方-x(x平方-3)-2x平方
答:
(x平方-3)平方-x(x平方-3)-2x平方
=(x²-3)²-x(x²-3)-2x² 利用十字相乘法:
=(x²-3-2x)(x²-3+x)
=(x-3)(x+1)(x²+x-3)
(x²-3)²-x(x²-3)-2x²
=[(x²-3)-2x][(x²-3)+x]
=(x²-2x-3)(x²+x-3)
=(x-3)(x+1)(x²+x-3)……没学二次根式的,到这一步就可以了。
=(x-3)(x+1)[(x+1/2)²-13/4]
=(x-3)(x+1)[x+(1+√13)/2][(x+(1-√13)/2]
(x平方-1)的平方-(2x+2)平方 (x平方+x)(x平方+x-2)-3(x平方-1)的平方-(2x+2)平方(x平方+x)(x平方+x-2)-3分解因式
化简:(x+y)平方-3(x平方-2y平方)
X平方-3x
x平方-3[2x-5(x平方-x+1)]
(x平方-3)平方-x(x平方-3)-2x平方
x的平方×(-x)的平方×(-2x的平方)+(-2x的平方)3次方
3x平方-5x平方y-{2x平方y+6xy平方-[2xy平方-3x平方y+(3x平方y-4xy平方】}
5x平方-[x平方 (5x平方-2x)-(2x平方-3x)]其中x=-2分之一
(1-x/3-x)平方除以x平方-6x+9/9-x平方*1/x平方-2x+1
(3x平方-4y平方)+[-(x平方-2xy-y平方)]-[(3x平方-2xy-y平方)]
(2x平方---3X立方Y平方Z)除3X平方Y平方
化简 -7X平方+6(X平方-5XY)-2(3xy平方-X平方)
已知3x平方+2y平方=6x 求x平方+y平方最大值
填空:2x平方-3x+( )=2(x+( )平方
|x平方-3|小于|x平方-2x|怎么解
2x平方-5x+x的平方+4x-3x的平方-2
(-2x平方+3x)-[5x-(2x平方+1)-x平方] 化简
方程2/X平方+X+3/X平方-X=4/X平方-1